2010
DOI: 10.1111/j.1365-3156.2010.02689.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunovirological outcomes and resistance patterns at 4 years of antiretroviral therapy use in HIV‐infected patients in Cambodia

Abstract: Summaryobjectives To report immunovirological outcomes and resistance patterns in adults treated with triple combination antiretroviral therapy (cART) for 4 years in an HIV programme of Phnom Penh, Cambodia.methods It is a longitudinal study and cross-sectional evaluation of adults receiving cART for 4 years. CD4 cell counts and HIV-1 RNA were quantified, and resistance patterns were determined. Drug-related toxicity was assessed by clinicians and through laboratory testing.results After 4 years of cART start,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
6
10
0
Order By: Relevance
“…This result is consistent with previous reports of studies conducted one to four years after the onset of first-line ARV regimen in Cambodia [27][31]. The VF rate observed after 4 year of ART was similar (4%) in another Phnom Penh hospital [30]. Interestingly, the VF rate reported herein is lower than that reported in sub-Saharan Africa patients where up to 24% of VF is obtained within 12 months of initiation of first-line ART [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with previous reports of studies conducted one to four years after the onset of first-line ARV regimen in Cambodia [27][31]. The VF rate observed after 4 year of ART was similar (4%) in another Phnom Penh hospital [30]. Interestingly, the VF rate reported herein is lower than that reported in sub-Saharan Africa patients where up to 24% of VF is obtained within 12 months of initiation of first-line ART [32].…”
Section: Discussionsupporting
confidence: 92%
“…All naive patients harbored viruses that were resistant to NVP/EFV with a majority of them showing the K103N/S mutation. The rates of 181C/I, K103N/S G190A and M184L/V mutations were also higher than in another recent study in Cambodia among patients having a median duration of 12 months up to 4 years on antiretroviral therapy [6], [7], [30]. The level of transmitted drug resistance (TDR) in naive patients needs to be assessed and could explain the high level of resistance mutations for this population potentially more recently infected than pre-treated patients.…”
Section: Discussionmentioning
confidence: 82%
“…A recent study in Vietnam conducted among 4531 adults and 313 children showed that 81.2 and 84.4%, respectively, were still on ART after 12 months [49]. This result was similar with the retention rate in Thailand (80.8% after 5 years) [45], Cambodia (80% after 4 years) [43] and higher compared to studies in sub-Saharan Africa with 24 months of follow-up: Uganda (72%) [36] and Malawi (66%) [37]. Other studies also showed that engagement of HIV care is associated with improved clinical, virologic and immunologic parameters and survival outcomes [50, 51].…”
Section: Discussion Virologic Failure Mortality and Retention Ratessupporting
confidence: 63%
“…Several studies on cohorts of HIV-infected patients receiving HAART in Thailand and Cambodia have been published but to date, there is no equivalent publication on the outcomes of patients on-HAART in Lao PDR [15-20]. To fill this gap, we conducted a retrospective analysis on a database made available to us by the Ministry of health/Center for HIV and STI and MSF in order to report the first results on patients receiving HAART at Savannakhet Provincial Hospital, located on the Thai-Lao border, between April 2003 and June 2009.…”
Section: Introductionmentioning
confidence: 99%